2013
DOI: 10.5812/jjm.6334
|View full text |Cite
|
Sign up to set email alerts
|

Mycoflora of Fungal Contamination in Wheat Storage (Silos) in Golestan Province, North of Iran

Abstract: Background: Cereal products are susceptible to mould damage during pre-and post-harvesting stages of the production. The regional specificity of Golestan province in the northern region of of Iran, with its high temperature and high relative humidity, acts as a leading factor for the growth of aflatoxin-producing fungi. It is well known that contamination of starch-based ingredients with mycotoxigenic fungi is a risk factor among the consumers due to its aflatoxins. Objectives: This survey was carried out to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
(13 reference statements)
1
9
0
Order By: Relevance
“…In one of the literatures of the previous research, presence of fungi was tested in 34 samples collected from 3 silos. Results of this experiment proved that presence of fungi produced aflatoxins in majority of tested samples [5]. It is worth mentioning that fungi represent the main factors of starchy grain contamination (mycotoxigenic).…”
Section: Bsupporting
confidence: 53%
See 1 more Smart Citation
“…In one of the literatures of the previous research, presence of fungi was tested in 34 samples collected from 3 silos. Results of this experiment proved that presence of fungi produced aflatoxins in majority of tested samples [5]. It is worth mentioning that fungi represent the main factors of starchy grain contamination (mycotoxigenic).…”
Section: Bsupporting
confidence: 53%
“…Despite all precautions taken in modern silos, many studies have shown that fungi are flourishing on wheat grains and in the air of these reservoirs [5]. Several research findings have confirmed the presence of harmful and toxic fungi in many silos, not only on stored grains but also on wheat flour derived from those silos.…”
Section: Bmentioning
confidence: 99%
“…If the storage conditions are unfavorable, these molds are factors of biological deterioration of the wheat affecting the quality of the raw materials, or the sanitary quality by the secretion of mycotoxins [55]. In other studies, Joshaghani et al [56] isolated seven strains from stored For the Alternaria spp1 strain; the extract showed a moderate activity which regresses with the augmentation of the concentration, but at the concentration of 1000 ppm, the negative effect appears (the increase of the growth of the mold compared to the control). All concentrations of Aloe Vera extract solutions have strong activity against Alternaria spp2 strain.…”
Section: Mold Isolationmentioning
confidence: 99%
“…Fungi such as species of Aspergillus, Penicillium, Rhizopus, Mucor etc., cause deterioration of stored commodities. Besides, these fungi also produce toxins such as aflatoxins and others which produce various symptoms on consumption (Amadi and Adeniyi, 2009;Keller et al, 2012;Joshaghani et al, 2013;Suleiman and Omafe, 2013). Fungicides have been extensively used for control of plant pathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%